Stability of a Ni-rich Ni-Ti-Zr high temperature shape memory alloy upon low temperature aging and thermal cycling. (November 2016) - Pérez-Sierra, A.M.; Pons, J.; Santamarta, R.; Karaman, I.; Noebe, R.D.
Abstract: The thermal stability of Ni50.3 Ti29.7 Zr20 with aging in austenite at 250 °C has been studied for three distinctive microstructures obtained after selected thermal treatments: precipitate free and containing two different sizes and densities of H-phase nanoprecipitates. The martensitic transformation is suppressed after 1–3 weeks aging, depending on the initial microstructure, due to a B2 phase instability in the form of short range atomic reordering within the Ti + Zr sublattice, considered to be precursor to the H-phase precipitation. Thermal cycling leads to notable changes in the transformation temperatures, which strongly depends on the starting microstructure. Graphical abstract: